Partnering with schools for community development: Power imbalances in rural community collaboratives addressing childhood adversity. Issue 2 (15th March 2018) - Biddle, Catharine; Mette, Ian; Mercado, Andrea
Abstract: Complex challenges such as toxic stress and childhood adversity require cooperation and collaboration between organizations – particularly schools – and communities in order to be addressed. However, schools can be challenging partners in place-based collaborations because of the ways in which they are beholden to external mandates and pressures from state and federal agencies. This qualitative case study examines how stakeholder groups participating in a community collaborative frame the goals, opportunities, and challenges of collaborating to address childhood adversity and toxic stress in a remote, rural context. Using a technique called affinity networks to visualize the valence of ideas and beliefs across their collaborative network, we identify shared frames for their work as well as specific sites of frame competition between school-based stakeholders and others. We suggest that these patterns indicate the importance of explicitly framing community collaborations that include schools in ways that ensure equitable participation, particularly of historically marginalized groups.